Wisdom Psalms in African Context with Special Reference to Nigeria - Adamo, David T. (Black Theology, 2015)
The study of the Psalter has been dominated by Western scholars. However, African biblical scholars and non-specialists have started to undertake serious studies on the book of Psalms. This paper attempts to discuss not only the Eurocentric and Africentric approaches to the book of Psalms that are classified as wisdom Psalms, but also some of the differences, similarities, and the need for cross-fertilization. Despite the fact that the Africentric approach may seem “strange” and even seem “magical” to some non-African scholars, it is a reality on the continent, and it is very much part of the existential challenges facing African people. Evidence from biblical archaeology seems to support the fact that ancient Israelites used the book of Psalms for protection, healing, and success in life, according to ancient Near Eastern Cultures. This supports the Africentric use of the wisdom Psalms.
paid